FUND OF ELIMINATION OF BOTTLENECKS - T. Gataullin; L. Goncharov; S. Nikolotova (Вестник университета, 2016)
Authors offer creation of new financial fund which main objective will be the solution of problems of the Russian society which complicate our everyday life. If to look back around - we are in a bunch of problems, the solution of many of which lies on a surface, and we only need to construct the mechanism of an embodiment of such decision in life.